Biochemical Toxicology - Heavy Metals and Nanomaterials 2020
DOI: 10.5772/intechopen.85157
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicology of Glyphosate-Based Herbicides on Aquatic Environment

Abstract: Glyphosate-based herbicides (GBHs) are chemicals developed to control unwanted plants such as weeds or algae. These chemicals act on EPSPS enzyme that blocks the production of tyrosine, phenylalanine, and tryptophan amino acids causing plant death. This biochemical pathway exists only in plant organisms. Despite the target use, GBHs have been related to toxic effects on nonplant organisms, such as invertebrates, fishes, amphibians, reptiles, birds, and mammals, including humans. This chapter is focused on ecot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 89 publications
(114 reference statements)
0
13
0
Order By: Relevance
“…The compound might also be genotoxic to cells, a fact substantiated by histopathological tests in fish hepatocytes where vacuolization and cytoplasm degradation were observed (Samsel and Seneffl, 2015 ). A biochemical analysis of the liver, heart, and kidneys conducted on freshwater fish Cyprinus Carpio L. documented an increase in the activity of alkaline phosphatase and the activity of glutamine-oxaloacetate transaminase (Gonçalves et al, 2019 ). Furthermore, GBH reduced the activity of antioxidant enzymes (such as catalase, glutathione peroxidase, and superoxide dismutase) in fish species like rainbow trout (Hidalgo et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The compound might also be genotoxic to cells, a fact substantiated by histopathological tests in fish hepatocytes where vacuolization and cytoplasm degradation were observed (Samsel and Seneffl, 2015 ). A biochemical analysis of the liver, heart, and kidneys conducted on freshwater fish Cyprinus Carpio L. documented an increase in the activity of alkaline phosphatase and the activity of glutamine-oxaloacetate transaminase (Gonçalves et al, 2019 ). Furthermore, GBH reduced the activity of antioxidant enzymes (such as catalase, glutathione peroxidase, and superoxide dismutase) in fish species like rainbow trout (Hidalgo et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, to mitigate side effects, governments have established limits on the usage and concentration of glyphosate-based pesticides in water reservoirs. For instance, the US permits 700 μg/l in tank water, Canada allows 280 μg/l in drinking water, while European regulations are more strict, permitting only 0.1 μg/l, thereby potentially offering more restrictive in terms of protecting aquatic biodiversity (Gonçalves et al, 2019 ). A study showed that concentrations of glyphosate below 0.1 μg/l present a low risk, while those above 1 μg/l – a level below the legal limit in some countries – pose a significant risk to aquatic organisms (Rehman et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it emerges that the most frequently tested heavy metals are copper (Cu), cadmium (Cd), chromium (Cr), and zinc (Zn), while the plant species that are most widely used to test their effects are listed in Supplementary Table 1. The most commonly detected responses by these species in the presence of heavy metals are: reduction in the growth rate, increase in the rate of necrosis and chlorosis, oxidative stress and photosynthesis inhibition (Monferran et al 2009;Razinger et al 2010;Upadhyay et al 2011;Corcoll et al 2012), increase in the content of malondialdehyde (e.g., Das et al 2016;Decou et al 2018), and antioxidant responses (Gonçalves et al 2019;Li et al 2018).…”
Section: Heavy Metalmentioning
confidence: 99%
“…Other processes that determine Gly fate are immobilization and leaching: the first one leads to soil adsorption/accumulation, while the second results in water contamination ( Bai and Ogbourne, 2016 ). Gly and AMPA are highly soluble in water and their persistence is variable depending on water conditions with half-lives ranging from few days to several weeks ( Tomlin, 2009 ; Grandcoin et al, 2017 ; ATSDR, 2020 ; Goncalyes et al, 2020 ). In soil, Gly and AMPA accumulate with a discrete persistence with half-lives depending on factors such as pH, salinity, microbial composition, spanning from few days up to about a year ( Bai and Ogbourne, 2016 ; Bento et al, 2016 ; Domínguez et al, 2016 ; Grandcoin et al, 2017 ; ATSDR, 2020 ).…”
Section: Introductionmentioning
confidence: 99%